Respuesta :

[tex]\huge\fcolorbox{blue}{aqua}{Answer:}[/tex]

═════════════════════

Answer: =A.[tex]x = - 3[/tex] [tex]x = - 4[/tex]

Solution:

[tex]x ^ { 2 } +7x=-12[/tex]

[tex]x^{2}+7x+12=0 [/tex]

[tex]a+b=7 ab=12 [/tex]

[tex]1,12 2,6 3,4 [/tex]

[tex]1+12=13 2+6=8 3+4=7 [/tex]

[tex]a=3 b=4 [/tex]

[tex]\left(x+3\right)\left(x+4\right) [/tex]

[tex]x = -3[/tex] , [tex]x = -4[/tex]

so the answer is = A.

════════════════════

Explanation:

#Carry on learning

Ask: Which two numbers add up to 7
7 and multiply to 12?
3 and 4

Rewrite the expression using the above.
(x+3)(x+4) = 0
x+3=0 or x+4=0
So x = -3 or x= -4